Productivity growth, technological change and Indian policy regime - Subrahmanian, K.K. (1998)
The focus of analysis in the paper is on the rationale of a policy regime in which the role of the State policy is redefined to correct market failures in tecnology transfer and to catalyse internal learning for improving domestic technological capability and economic growth. More specifically, the paper reviews trends in productivity growth in the Indian manufacturing sector under different polity regimes during the last 30 years and highlights some uneasy issues connected with technology transfer under a liberal and open-door policy regime. The paper concludes that technological change both under closed-and open-door policies could raise productivity and growth, but of qualitatively different types. Perhaps, a developing country like India should have a proper mix of market competition and State policy modes in relation to technological change and economic development. - Reproduced
Keywords: Economic growth - India; Economic growth